Regeneration efficiency of cowpea [Vigna unguiculata (L.) Walp.] via embryonic axes explants - Yusuf, M.; Raji, A.A.; Ingelbrecht, I.L.; Katung, M.D. (2008)
The experiment was conducted to test the in vitro regeneration efficiency of cowpea shoots via embryonic axes explants and the effect of benzyl amino purine (BAP) concentration on shoot formation. A total of 600 explants (embryonic axes) were plated from which 237 shoots were regenerated. The average regeneration ratio was 39% and the number of shoot per explant obtained stood at an average of 6.0. This indicates likelihood that higher regeneration percent and number of shoots per explant could be possible as more proficiency is attained in the use of the protocol. The role of the growth regulator, benzyl amino purine (BAP), as a shoot growth inducing factor and modifier in cowpea in vitro regeneration was demonstrated in the experiment. The protocol used in the experiment gave promising results for the efficient regeneration and subsequent genetic transformation of cowpea.